The Paradox of Power: CEO Narcissism as a Driver of Accounting Conservatism - Elis Nur Faida; ani wilujeng suryani (Politeknik Negeri Batam, 2026)
This study examines how CEO narcissism and CEO education level influence accounting conservatism in Indonesian companies based on Upper Echelon Theory. The sample consists of 1,470 firm-year observations from energy, industrials, consumer non-cyclicals, basic materials, transportation & logistics, healthcare, property & real estate, technology, and infrastructure sectors listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Accounting conservatism is treated as the dependent variable, while CEO narcissism and CEO education level are the independent variables. Multiple regression results indicate that both CEO narcissism and CEO education level positively affect accounting conservatism, suggesting that highly self-confident CEOs and those with stronger educational backgrounds tend to apply greater prudence in financial reporting. These findings strengthen Upper Echelon Theory by demonstrating that CEO individual characteristics can shape more conservative accounting policies. The study also provides practical implications for companies and stakeholders in maintaining financial reporting quality and credibility.